The baseball birthday party - Prager, Annabelle; Mets, Marilyn (New York : Random House, 1995)
Billy decides to have a party to show the other kids that he can play baseball, but his young helper's mistake almost spoils the plan.
"A step 2 book grades 1-3."--Cover.
11 13 19 23 29 31
Keywords: Baseball -- Fiction; Parties -- Fiction